Associations of sugar-sweetened beverage knowledge, self-efficacy, and perceived benefits and barriers with sugar-sweetened beverage consumption in adolescents: A structural equation modeling approach. (1st January 2022) - Wang, Chia-Wen; Chen, Duan-Rung
Abstract: This study was performed to investigate the predictors of sugar-sweetened beverage (SSB) consumption in adolescents, including knowledge of SSBs, self-efficacy, and perceived benefits and barriers, using the structural equation modeling approach. This cross-sectional study was conducted from March to June 2019 in New Taipei City, Taiwan. The participants were 633 adolescents from 23 classes at three junior high schools in New Taipei City. A structured self-administered questionnaire was developed for data collection. The overall model predicted SSB consumption well, suggesting that SSB consumption was associated with self-efficacy and perceived barriers and benefits. Self-efficacy was the strongest predictor of SSB consumption. Both perceived barriers and self-efficacy sequentially and fully mediated the effect of knowledge on SSB consumption. This study confirms that self-efficacy is associated with SSB intake in both male and female adolescents. However, knowledge of SSBs was not associated with SSB consumption. Relying on nutritional education alone may not be adequate to change SSB consumption. The results suggest that future health promotion programs should improve self-efficacy to decrease SSB consumption in adolescents.